SERUM BIOCHEMICAL AND HEMATOLOGICAL PROFILE OF MALE, FEMALE AND DIFFERENT AGE GROUPS OF KRISHNAVALLEY BREED OF CATTLE IN KARNATAKA - K.SRIPAD,; SHRIKANT KOWALLI,; RAJU METRI, (International Journal of Pharma and Bio Sciences, 2014)
Krishnavalley breed of cattle is an indigenous breed of black soil along the river basin of Krishna predominantly and also Ghataprabha, Malaprabha and Tungabhadra rivers in Karnataka. Present study was conducted at Belgaum and Koppal districts of Karnataka and describes the normal reference values of serum biochemical and hematological parameters in male, female and also in different age groups (0-3 years, 3-6 years and 6-9 years) of Krishnavalley breed of cattle. Fifteen blood samples each were collected from male and female and ten samples each were collected from different age group of animals, taking all aseptic precautions. Serum biochemical and hematological parameters were determined, statistically analyzed and set as reference values for male, female and different age groups of animals, which serve as baseline values for comparison of normal, various physiological, nutritional and deficiency conditions in male, female and also for different age groups of Krishnavalley breed of cattle.